Combined treatment of prednisone and hydroxychloroquine may improve outcomes of frozen embryo transfer in antinuclear antibody-positive patients undergoing IVF/ICSI treatment. (December 2021) - Gao, Rui; Deng, Wei; Meng, Cheng; Cheng, Kemin; Zeng, Xun; Qin, Lang
Background: The influence of anti-nuclear antibody (ANA) on induced ovulation was controversial, and the effect of prednisone plus hydroxychloroquine (HCQ) treatment on frozen embryo transfer outcomes of in-vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) for ANA-positive women was unclear. Methods: Fifty ANA-positive women and one-hundred ANA-negative women matched for age and anti-Mullerian hormone (AMH) were included from a Reproductive Medical Central of a University Hospital. Sixty-one oocytes pick-up (OPU) cycles in ANA+ group and one-hundred OPU cycles in ANA− group were compared; 30 frozen embryo transfer cycles without treatment and 66 with prednisone plus HCQ treatment among ANA-positive women were compared. Results: There was no statistical difference in number of retrieved oocytes (13.66 ± 7.71 vs 13.72 ± 7.23, p = .445), available embryos (5.23 ± 3.37 vs 5.47 ± 3.26, p = .347), high-quality embryos (3.64 ± 3.25 vs 3.70 ± 3.52, p = .832), and proportion of high-quality embryos (26.5% vs. 26.7%, p = .940). Biochemical pregnancy rate (33.3% vs. 68.2%, p < .05), clinical pregnancy rate (20.0% vs. 50.1%, p < .05), and implantation rate (5.6% vs. 31.8%, p < .05) were lower, and pregnancy loss rate (83.3% vs. 23.1%, p < .05) was higher in patients with treatment than no treatment. Conclusion: The influence of ANA on number of retrieved oocytes, available embryos, high-quality embryos, and proration of high-quality embryos was not found. The treatment of prednisone plus HCQ may improve implantation rate, biochemical pregnancy rate, and clinical pregnancy rate, and reduce pregnancy loss rate in frozen embryo transfer outcomes for ANA-positive women.